Effect of hot climate of Saudi Arabia on physical and mechanical properties of single use polypropylene packaging films - Aravinthan Gopanna; Selvin P. Thomas; Krishna Prasad Rajan (Yanbu Journal of Engineering and Science)
Two types of single use plastic films were used to study the effect of hot climate conditions of Saudi Arabia during a six-month experiment. The objective of the study is to understand the degradation behavior of the single use packaging films under direct sunlight exposure with variation in humidity. The films were kept on a specially designed experimental setup. The films were analyzed every month with respect to morphology, spectroscopy, thermal and mechanical properties. The microscopic images showed initiation of cracks on the exterior of films. Mechanical properties such as tensile strength and tensile modulus were measured and a decrease of 17 and 7% from the virgin material was noticed. The thermal and flammability properties also showed a decrease which confirmed the ageing of the films due to the climatic conditions. The water contact angle showed 20% decrease which indicated the effect of the weathering conditions to make the films less hydrophobic. The degraded packaging films after the exposure could be used as recycling component for the preparation of reusable single use plastic compounds.